Plasma progesterone concentration during oestrus cycle and pregnancy in Finnsheep and other prolific sheep breeds - Reklewska, B.; Tyszka, Z. J.; Niznikowski, R. (Agricultural and Food Science, 1988)
The aim of the study was to evaluate the relationship between the litter size and plasma progesterone (PP) concentration during the breeding season and pregnancy in some prolific sheep breeds. Investigations were performed during two consecutive reproductive cycles. PP concentrations were determined in Finnsheep (n = 16), Polish Heath (n = 13), Friesian (n = 10), Zelazna (n = 12) and Karakul (n = 14). Prolificacy was 3.14, 2.0, 2.0, 1.8 and 1.12, resp. Highly significant differences in PP levels during pregnancy were found between the prolific breeds and breed with the lowest litter size. There was also a significant effect of pregnancy stage on the PP concentration. Breed differences in PP levels during the oestrus cycle were the most pronounced on the 10th day of the cycle. However, due to a considerable variation within breeds they were statistically insignificant.